Self-assembled monolayers of perfluoroterphenyl-substituted alkanethiols: specific characteristics and odd-even effects - Chesneau, Frédérick; Schüpbach, Björn; Szelągowska-Kunstman, Katarzyna; Ballav, Nirmalya; Cyganik, Piotr; Terfort, Andreas; Zharnikov, Michael (Physical chemistry, chemical physics, 2010)
Self-assembled monolayers (SAMs) formed by perfluoroterphenyl-substituted alkanethiols (C6F5-C6F4-C6F4-(CH2)n-SH, FTPn) with variable length of the aliphatic linker (n = 2 and 3) were prepared on (111) Au and Ag and characterized by a combination of several complementary spectroscopic and microscopic techniques. A specific feature of these systems is the helical conformation of the FTP moieties, which, along with the high electronegativity of fluorine, distinguishes them from the analogous non-fluorinated systems and makes them attractive for different applications. The SAMs were found to be well-defined, highly ordered, and densely packed, which suggests a perfect correlation between the orientations and, in particular, twists of the FTP helices in the adjacent molecules. Significantly, the SAM exhibited pronounced odd-even effects, i.e. a dependence of the molecular orientation and packing density on the length of the aliphatic linker in the target molecules, with parity of n being the decisive parameter and the direction of the effects on Au opposite to that on Ag. The presence of the odd-even effects in the FTPn system brings new aspects into the discussion about the origin and mechanism of these phenomena. Specifically, the helical conformation of the FTP moieties in the dense phase excludes a variation of the intramolecular torsion and molecular twist as the mechanism behind the odd-even effects.
Gesehen am 08.03.2023